The Role of Service Marketing Elements on Customer Loyalty towards Garuda Indonesia - Andrian Gunawan (iBuss Management, 2015)
Service Marketing mix is one of many important factors for service based companies to be able determining the strategy of the company. The elements in the service marketing mix is believed to lead to customer loyalty toward a brand. Garuda Indonesia, which is one of the airline companies in Indonesia, has to compete with other airline companies in order to attract customers and keep them loyal to their product. In this research, the data is obtained by using simple random sampling method by distributing questionnaires to some respondents in Surabaya. Then, the data is analyzed by using Multiple Linear Regression Analysis. The result is expected to be able showing that the service marketing mix has a significant influence on customer loyalty.Keywords: Service Marketing Mix, Customer Loyalty, 7Ps, Multiple Linear Regression